Access to finance for SMEs in Albania under monetary tightening - Elona Dushku (Graduate Institute of International and Development Studies, 2025)
Small and medium-sized enterprises (SMEs) are vital to Albania's economy but face significant financing challenges amid monetary tightening. Utilizing firm-level data from 2022-2023, this study documents that the abrupt interest rate increases in 2022 prompted a rise in alternative financing use, particularly among younger and smaller firms, alongside greater reliance on internal funds as an immediate coping mechanism. In contrast, the more gradual tightening in 2023 led to a broad-based decline in both alternative and internal financing, indicative of constrained liquidity and persistent financial pressures across firms. Notably, heterogeneity in internal financing adjustments was limited, with younger firms showing no statistically significant difference from older firms, except for those experiencing tighter bank credit conditions, who further curtailed internal funding. These findings underscore the varied responses of SMEs to phased monetary tightening and emphasize the need for targeted policy measures to support firm resilience over time.
Keywords: E52; G21; G32; L25; 330; SMEs; Access to Finance; Monetary Tightening; Firm Characteristics